STEM-PjBL dan Kaitannya dengan Kompetensi 6C dalam Penelitian Pendidikan Fisika: Analisis Bibliometrik - Winda Putri; Rasyid Zuhdi; Andika Febrian; Andyta Usnia; Aziza Karenina; Nuris Fatahillah (Jurnal Kajian Pendidikan IPA, 2026)
The era of disruption that requires 21st-century skills as a provision in facing real-world challenges, including the world of work and the demands of global society, is the main background of this research. The 21st-century skills in question refer to the 6C competencies (citizenship, critical thinking, creativity, collaboration, and communication). The main objectives of this study are to map the relationship between STEM-PjBL in physics learning with the 6C competency, find research gaps based on the mapping, and provide recommendations for educators related to 21st-century skills-oriented learning. Therefore, this study is included in the category of literature studies using bibliometric analysis assisted by the VOSViewer application. The articles related to the keywords STEM-PjBL and the 6C competencies were compiled through the Scopus and Google Scholar databases with the help of the Publish or Perish application. The pattern generated from 968 data shows that the trend of research on STEM-PjBL in the period 2015-2025 tends to increase. In addition, the network visualization pattern also shows that STEM-PjBL is related to the 6C competencies, but it is still an area that is rarely studied. VOSViewer's items don't include character and citizenship as part of the 6C competency. This means that this is a novelty of research and a challenge for future research on how to holistically practice 6C competencies in learning. Project-based learning with a STEM approach is recommended as a tool to train 6C competencies, or 21st-century skills, as the findings of various studies show that STEM-PjBL has a multidimensional impact on learning.Keywords: 6Cs Competency, 21st-century skills, PjBL, STEM